Impact of Seborrheic Dermatitis on Quality of Life: A Systematic Review and Meta Analysis - Chen, Jiaqi; Li, Carmen; Polaskey, Meredith; Chang, Christy; Chovatiya, Raj (Dermatology Practical & Conceptual, 2026)
Background: Seborrheic dermatitis (SD) is a common, chronic relapsing inflammatory skin condition associated with itch, cutaneous erythema and scaling, and multifactorial pathophysiology. Yet, there are conflicting reports of its impact on patient quality of life (QoL). Objectives: To address this gap a systematic review and meta-analysis was conducted to evaluate the health-related QoL impairment among individuals with SD. Methods: Comprehensive searches were performed in Embase, PubMed, Scopus, Cochrane, and CINAHL databases for publications available up to August 2024. Original studies in English that reported qualitative QoL measurements of SD were included. Following PRISMA guidelines, data were extracted and analyzed using the Metafor package in R. Results: From an initial pool of 2,165 non-duplicated articles, 26 studies met the inclusion criteria. These studies consistently highlighted the mental, physical, and psychosocial challenges faced by SD patients, with baseline pooled Dermatology Life Quality Index (DLQI: 16 studies; n=3,812; 7.2 [95% CI: 6.3-8.1]) Skindex-29 (3 studies; n=2,501; 26.0 [16.9-35.1]) showing a moderate impact on QoL via random-effect model meta-analysis, with high study heterogeneity (I2 = 97-98%). Pooled Skindex-29 subdomain scores suggested highest impact on the symptoms subdomain. Increasing QoL impact was moderately associated with increasing SD severity (pooled r: 0.37 [95% CI: 0.31–0.43]; p=0.03). Conclusions: SD patients reported moderately impaired QoL which was positively associated with disease severity in pooled meta-analysis using multiple validated QoL instruments. These data highlight the patient impact of seborrheic dermatitis, with additional studies needed to better understand the multidimensional burden in order to optimize patient outcomes.